Inkjet 3D printing of UV and thermal cure silicone elastomers for dielectric elastomer actuators - McCoul, David; Rosset, Samuel; Schlatter, Samuel; Shea, Herbert (Smart materials and structures, 2017)
Dielectric elastomer actuators (DEAs) are an attractive form of electromechanical transducer, possessing high energy densities, an efficient design, mechanical compliance, high speed, and noiseless operation. They have been incorporated into a wide variety of devices, such as microfluidic systems, cell bioreactors, tunable optics, haptic displays, and actuators for soft robotics. Fabrication of DEA devices is complex, and the majority are inefficiently made by hand. 3D printing offers an automated and flexible manufacturing alternative that can fabricate complex, multi-material, integrated devices consistently and in high resolution. We present a novel additive manufacturing approach to DEA devices in which five commercially available, thermal and UV-cure DEA silicone rubber materials have been 3D printed with a drop-on-demand, piezoelectric inkjet system. Using this process, 3D structures and high-quality silicone dielectric elastomer membranes as thin as 2 m have been printed that exhibit mechanical and actuation performance at least as good as conventionally blade-cast membranes. Printed silicone membranes exhibited maximum tensile strains of up to 727%, and DEAs with printed silicone dielectrics were actuated up to 6.1% area strain at a breakdown strength of 84 V m−1 and also up to 130 V m−1 at 2.4% strain. This approach holds great potential to manufacture reliable, high-performance DEA devices with high throughput.